SYNTHESIS AND BIOLOGICAL ACTIVITY OF QUINAZOLIN-4-ONE HYDROCHLORIDE - Хайдаров Гайрат Шойимович; Saitkulov Foziljon Ergashevich; Тилябов Максуджон Умурзокович; Холмирзаев Мехрож Муродуллаевич; Элмурадов Бурхон Жураевич (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
By the interaction of anthranilic acid with formamide, an almost quantitative yield of quinazoline-4-oh was obtained. Optimal reaction conditions were established: temperature 130-140 °C, duration 2 hours. Quinazoline-4-oh hydrochloride was obtained from quinazoline-4-oh by passing hydrogen chloride with 96% yield. These compounds at a dose of 100-150 mg/kg exhibit 92% anthelmintic activity against fascioles common in cattle, sheep and goats.